Let f be defined by
f(x) = 2 - x if x <= 1
f(x) = 2x - x^2 if x > 1
Calculate f(-3) + f(0) + f(3).
plug -3 into the first equation, 0 into the first one as well, and 3 into the second one in order to meet all the conditions of the two functions.
This is a general thing about piecewise functions-- in this particular case, if x is any value less than or equals 1, you would plug x into the first equation.
f(-3)=5, f(0)=2, and f(3)=6-3^2=-3.
Adding them all up together we get the answer 4.
Hope this helps